Synarchizm meksykański 1931–2008: geneza, dzieje, doktryna. Część I do 1944 roku - Bartyzel, Jacek (Wydawnictwo Uniwersytetu Wrocławskiego, 2009)
The subject of this article is the history and social-and-political doctrine of the Catholic and nationalist civic movement operating for several dozen years in Mexico under the name of the “National Synarchist Union” Union Nacional Sinarquista. This paper constitutes the first part of the larger whole and encompasses the period of creation and of biggest dynamics of this movement 1937–1944, up until the split which resulted in its division into two factions. They use the same name – UNS – but they are popularly, for the purpose of differentiation, called UNS–MTB and UNS–CAC from the initials of their first leaders or “independent” independiente UNS and “dissident” UNS disidente. The presentation of the synarchism’s ideology and activities is prefaced by a brief outline of Mexican history, especially since the outbreak of so-called Mexican Revolution which led directly to the increasing persecution of Catholic religion and Church and indirectly to the outbreak and continuance 1926–1929 of the popular insurgency which is remembered by history by the name of guerra cristera or cristeros insurgency. The origins of synarchism are demonstrated here as a result, on the one hand, of negative repercussions of the agreement made by Church hierarchy with state authorities which did not bring about the end of persecution, and, on the other hand, of the necessity – which faced Mexican Catholics – of changing the way of defending their rights from armed struggle to civil struggle. This change was not to take place on the parliamentarian ground which was closed anyway by the de facto one-party system but in the civic sphere. In this context the article discussed the “prehistory” of the movement when the secret, hierarchical and national organization subordinated to bishops’ authority, fi rst called the Legion La Legion and later the Base La Base, was actively operating since the beginning of the thirties. UNS was directly created as a result of transformation of the Section 11 civic-and-social of the Base into a mass and overt civic movement. In its main part this paper concentrates on the presentation of the ideological principles of synarchism el sinarquismo. This name is derived from synarchia neologism which is made by connecting Greek words syn “with” or “together” and archein “to rule” or “to govern”. It is an antonym to the word anarchia. Synarchism desires society to be ruled by legitimate authority autoridad legitima which emerges from the spontaneous democratic activity of the nation emanada de la libre actividad democratica del pueblo and serves the common good bien comun. The main ideological principles declared by synarchists are: Christian social order, the good of the homeland, social peace, social justice, fight against Freemasonry and communism. The motto of synarchism consists of “three shiny words tres palabras luminosas: Homeland, Justice, Liberty” Patria, Justicia y Liberdad. The article also discusses the activities undertaken by UNS in the above-mentioned period, when the organization had almost half a million members, particularly the utopian project of building a synarchists’ colony in the wild named Maria Auxiliadora Mary the Helping One which was supposed to be a laboratory for the Synarchist State Estado Sinarquista. It also considers and refutes the hypothesis of “Nazi conspiracy” as an origin of the movement and presents the profiles of its leaders and ideologues, particularly of the charismatic “Chief Founder” Jefe Fundador and “First Martyr” Proto-Martyr Jose Antonio Urquiza Septien 1905–1938 and of Salvador Abascal Infante 1920–2000, the “National Chief” Jefe Nacional during the period of movement’s peak development.
Keywords: Mexico; synarchism; doctrine; history